Exercise-induced hyperkalemia and concentration of Na,K-pumps in skeletal muscle in mitral stenosis: effect of balloon mitral valvotomy. - Barlow, C; Long, J; Manga, P; Meyer, T; Paterson, D; Robbins, P (1999)
BACKGROUND AND AIMS OF THE STUDY: The study aim was to examine the effects of balloon mitral valvotomy (BMV) on exercise-induced hyperkalemia, and on changes in the concentration of Na,K-pumps in skeletal muscle, as an exaggerated exercise-induced rise in potassium concentration ([K+]) may contribute to exertional fatigue and breathlessness. METHODS: Eight subjects were evaluated with mitral stenosis (mean age 34 +/- 5.2 years) before, and at two weeks and four months after BMV. Subjects underwent incremental exercise to exhaustion for exercise-induced rise in [K+] and vastus lateralis biopsy for concentration of Na,K-pumps. RESULTS: Mean (+/- SE) valve area increased from 0.89 +/- 0.03 cm2 before to 1.75 +/- 0.05 cm2 after BMV. There was a progressive increase in VO2,max (15.3 +/- 1.6, 17.2 +/- 1.4 and 19.9 +/- 1.9 l/kg/min) at baseline, early after and later after BMV, respectively (p < 0.01). The rise in [K+] with absolute workload fell progressively at early and late follow up post-BMV (p < 0.05), but was unchanged when plotted against percentage of VO2,max to match for relative workload. The concentration of Na,K-pumps was similar to baseline at early follow up (233 +/- 10 versus 228 +/- 15 pmol/g wet weight), but was significantly increased at late follow up after four months (265 +/- 17 pmol/g; p < 0.05). When the relationship between the concentration of Na,K-pumps and the exercise-induced rise in [K+] was studied, a negative correlation was found. However, correlation analysis for the effects of changes in Na,K-pumps on changes in exercise hyperkalemia after BMV was not significant. CONCLUSIONS: The progressive reduction in exercise-induced rise in [K+] after BMV may contribute to the progressive improvement in exercise performance. The increased concentration of Na,K-pumps in skeletal muscle may assist in this improvement, and emphasizes the importance of peripheral adaptations in clinical improvement after BMV.